2007
DOI: 10.4049/jimmunol.179.12.8016
|View full text |Cite
|
Sign up to set email alerts
|

Altered Distribution of H60 Minor H Antigen-Specific CD8 T Cells and Attenuated Chronic Vasculopathy in Minor Histocompatibility Antigen Mismatched Heart Transplantation in Cxcr3−/− Mouse Recipients

Abstract: Chemokine-chemokine receptor interactions and the subsequent recruitment of T lymphocytes to the graft are believed to be among the initial events in the development of acute and chronic rejection of heart transplants. We sought to determine the role of chemokine receptor Cxcr3 on the development of acute and chronic rejection in a multiple minor Ag mismatched mouse heart transplant model. The frequencies and kinetics of immunodominant H60 (LTFNYRNL) miHA-specific CD8 T cells in wild-type or Cxcr3−/− C57BL/6 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…IFN-␥ elicited chemokines, such as IP-10 and MIG, may also contribute to inflammation by recruiting IFN-␥ producing T cells. We showed that reduced infiltration of CD8 T cells in a CR model using CXCR3 Ϫ/Ϫ mice alleviated CR (26). In accordance with this, induction of IFN-␥ inducible chemokine transcripts (such as MIG, IP-10, I-TAC, and RANTES) in endomyocardial biopsies showed an association with the development of graft arteriosclerosis (27)(28)(29).…”
Section: Adaptive Immunitysupporting
confidence: 77%
See 2 more Smart Citations
“…IFN-␥ elicited chemokines, such as IP-10 and MIG, may also contribute to inflammation by recruiting IFN-␥ producing T cells. We showed that reduced infiltration of CD8 T cells in a CR model using CXCR3 Ϫ/Ϫ mice alleviated CR (26). In accordance with this, induction of IFN-␥ inducible chemokine transcripts (such as MIG, IP-10, I-TAC, and RANTES) in endomyocardial biopsies showed an association with the development of graft arteriosclerosis (27)(28)(29).…”
Section: Adaptive Immunitysupporting
confidence: 77%
“…In accordance with this, several groups showed a beneficial effect of targeting these chemokine receptors on CR (86 -90). We also showed that Cxcr3Ϫ/Ϫ knockout mouse recipients of cardiac allografts showed reduced neointimal hyperplasia with less CD8 T-cell infiltration (26). Combined blockade of Cxcr3/Ccr5 showed a beneficial effect on chronic allograft vasculopathy in the setting of a full MHC full mismatch (91).…”
Section: B-cell Biologicsmentioning
confidence: 68%
See 1 more Smart Citation
“…However, several recent reports have not been able to reproduce similar beneficial effects. Two independent groups have reported that CXCR3 −/− and control mice reject full MHC mismatched donor hearts at the same rate 115, 116. These studies also showed that T-cell infiltration into the rejected hearts were similar in the 2 groups.…”
Section: Chemokine - CXC Chemokine Receptormentioning
confidence: 79%
“…B6 heart transplantation. 12,19 As shown in Figure 2B, peripheral H60-specific CD8 T cells from untreated animals (POD 10) demonstrated homing (CD11a hi CD44 hi CD62L lo ) and chemokine (Cxcr3 + Ccr5 + Ccr7 − ) receptor expression of a traditionally activated Th1-related cell phenotype. Through the combination of this homing/chemokine receptor expression, these cells are immunophenotypically ready to leave the secondary lymphoid organ and get to the inflammatory site.…”
Section: Lfa-1 Blockade Profoundly Suppresses Immunodominant H60-specmentioning
confidence: 89%